2006
DOI: 10.1189/jlb.0306229
|View full text |Cite
|
Sign up to set email alerts
|

Calcitonin gene-related peptide inhibits early B cell development in vivo

Abstract: Recent in vitro studies suggest that calcitonin gene-related peptide (CGRP) inhibits early B cell differentiation; however, there is no evidence in the intact animal for a role for CGRP in B cell development. Here, we show that in vivo treatment of mice with CGRP reduces the number of IL-7 responsive B cell progenitors in bone marrow. A single CGRP treatment reduces IL-7-responsive B cell progenitors by up to 40% for up to 72 h. The reduction is dose-dependent and can be blocked by a CGRP receptor antagonist, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…CGRP inhibited the expression of surface immunoglobulin in response to LPS (McGillis et al, 1993, 1995). These studies suggest a crucial role for CGRP in early B cell differentiation, a finding supported by later studies (Fernandez et al, 2000; Schlomer et al, 2007). …”
Section: Cgrp Regulates Lymphocyte Differentiation and Cytokine Produsupporting
confidence: 66%
“…CGRP inhibited the expression of surface immunoglobulin in response to LPS (McGillis et al, 1993, 1995). These studies suggest a crucial role for CGRP in early B cell differentiation, a finding supported by later studies (Fernandez et al, 2000; Schlomer et al, 2007). …”
Section: Cgrp Regulates Lymphocyte Differentiation and Cytokine Produsupporting
confidence: 66%
“…B cells can respond to treatment with CGRP in vitro , and CGRP hinders development of B cell precursors. Blocking CGRP receptors with the peptide antagonist CGRP8-37 prevented this CGRP-driven inhibition ( 136 ).…”
Section: Immune Cells In the Meningesmentioning
confidence: 99%
“…For instance, the peptide pA20-−36 could bind to the B-cell receptor (BCR) of A20 cells, 72 and the calcitonin gene-related peptide could inhibit early B-cell development. 73 In this study, CY highly depressed LPS-induced splenocytes proliferation, as shown in Figure 9. AC8 peptide could not increase the splenocytes proliferation induced by LPS in the mice treated by CY.…”
Section: ■ Results and Discussionmentioning
confidence: 89%